Influence of Assist Tug Ship Operation Time and Service Rates Pandu-Delay Against The Performance of PT. Delta Mandiri Batam Shipping - Awanda, Deta; Malau, April Gunawan; Lestari, Widianti (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Guiding is part of the navigation or support function in the safety of ship navigation which is caused by the unique characteristics of the port. Quantitative research is a type of research that uses numbers in processing data to produce structured information. Characteristics of quantitative research using the SPSS application, aims to obtain data that describes the characteristics of objects, events or situations (Sekaran & Bougie, 2016:43). Based on partial hypothesis testing, it is known that the assist tug variable has a positive and significant effect on PT performance. Delta Mandiri Batam. This is proven by 0.002 0.05 and a tcount value of 2,343 ttable 1,697. Tug Assist Contribution to Performance 0.305. So it can be concluded that the first hypothesis in this research is accepted. This shows that the more reliable and accurate the quality of service provided by employees during the assist tug process at PT. Delta Mandiri Batam means there will be no quality of service rates for tug-guide services and performance. The influence of assist tug ship operating time has been proven to have a positive and significant effect on performance at the company PT Pelayaran Delta Mandiri Batam, with a regression coefficient of 0.027 and a t-value of 2.343, t -table 1,697.